Social Psychological Conditions for the Development of Professional Reflection in Internal Affairs Psychologists (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
In this article, the development of the process of reflection in personnel working as psychologists and the factors of formation of the professional culture of the employees of the internal affairs bodies, professional ethics, culture of behavior, rules of conduct, the conditioning of the formation of a psychological portrait and the obligations that each employee must follow are discussed. will go.